2017
DOI: 10.1111/jcmm.13143
|View full text |Cite
|
Sign up to set email alerts
|

Selective blockade of B7‐H3 enhances antitumour immune activity by reducing immature myeloid cells in head and neck squamous cell carcinoma

Abstract: Immature myeloid cells including myeloid‐derived suppressor cells (MDSCs) and tumour‐associated macrophages (TAMs) promote tumour growth and metastasis by facilitating tumour transformation and angiogenesis, as well as by suppressing antitumour effector immune responses. Therefore, strategies designed to reduce MDSCs and TAMs accumulation and their activities are potentially valuable therapeutic goals. In this study, we show that negative immune checkpoint molecule B7‐H3 is significantly overexpressed in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 53 publications
(63 reference statements)
3
34
0
Order By: Relevance
“…In this article, we revealed that the expression of LAIR‐1 was positively related to IDO. Several studies have established that immune checkpoints, such as PD‐1 (programmed death‐1), B7‐H3 (B7 homolog 3 protein), and VISTA (V‐domain Ig suppressor of T cell activation), are drivers of immune suppression in OSCC . We also observed a significant correlation with the expression of LAIR‐1 and B7‐H3 and VISTA.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In this article, we revealed that the expression of LAIR‐1 was positively related to IDO. Several studies have established that immune checkpoints, such as PD‐1 (programmed death‐1), B7‐H3 (B7 homolog 3 protein), and VISTA (V‐domain Ig suppressor of T cell activation), are drivers of immune suppression in OSCC . We also observed a significant correlation with the expression of LAIR‐1 and B7‐H3 and VISTA.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have established that immune checkpoints, such as PD-1 (programmed death-1), B7-H3 (B7 homolog 3 protein), and VISTA (V-domain Ig suppressor of T cell activation), are drivers of immune suppression in OSCC. 5,15,36,37 We also observed a significant correlation with the expression of LAIR-1 and B7-H3 and VISTA. Taken together, we suspect that LAIR-1 is likely to exert immune suppressive function in OSCC and may serve as a therapeutic target in combination with other immune checkpoints.…”
Section: Discussionsupporting
confidence: 61%
“…Its exact mechanisms are still unknown but there is evidence for co‐stimulatory and co‐inhibitory signalling for adaptive immune system activation under different tumour contexts (Wang, Kang, & Shan, ). Although B7‐H3 was studied only twice in OSCC for its prognostic value (Chen, Chen, et al, ; Chen, Wu, et al, ; Mao et al, ), it was more promising than the other molecules as a prognostic marker as both studies reported consistent evidence for its prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report shows that blockade of B7-H3 decreases tumor size and increases the number of CD8 + tumor infiltrating lymphocytes in syngeneic models of pancreatic cancer and lung cancer. 43 Another report indicates that antibody-mediated inhibition of B7-H3 reduces tumor growth as well as the number of tumor associated macrophages and myeloid derived suppressor cells in genetic 44 The utility of B7-H3 as a therapeutic target is further supported by a recent report using xenograft and allograft models of various carcinomas to demonstrate the efficacy of B7-H3 antibody-drug conjugates (ADCs) to successfully target both tumor cells and tumor associated vasculature, prolong survival, and reduce metastasis. 35 As it pertains to osteosarcoma, our data showing that increased B7-H3 expression correlates with poor survival is consistent with that of Wang et al, collectively indicating that this molecule may be an attractive immunotherapeutic target in this disease.…”
Section: Discussionmentioning
confidence: 99%